Parallel hydraulic pressure assist/work circuit hybrids for automated side loader refuse vehicles - Echter, Nicholas, author; Bradley, Thomas, advisor; Babbitt, Guy, committee member; Young, Peter, committee member (Colorado State University. Libraries, 2012)
Hydraulic hybrids have been a subject of study for some time now and the application of these hybrids to refuse vehicles has been thoroughly explored. There is a lesser known subset of these which are known as pressure assist or work circuit hybrids that have unique potential to the field. Work circuit hybrids operate similar to a parallel hydraulic hybrid in that energy is captured and stored during regenerative braking. These hybrids differ in that the energy is then used to operate the hydraulic cylinders that handle and compact the refuse rather than reaccelerating the vehicle. Work circuit hybrids can be applied to many types of vehicles but the refuse vehicle application is the focus of this study. It was known prior to this study that work circuit hybrids are a potential solution to improve the fuel economy of refuse vehicles. However, prior to this study, the design of a work circuit hybrid had not been outlined in the literature. It was the goal of this thesis to answer the following questions. What are the fuel economy and cost characteristics of an optimized work circuit hybrid, and can an advanced hydraulic work circuit design justify further development towards productization? To answer these questions the study began by exploring, at a high level, the feasibility of work circuit hybrids on refuse vehicles. Then, two automated side loader, 28 cubic yard (21.4 m3), McNeilus Street Force MA refuse vehicles that operate on residential routes throughout Denver's surrounding areas were instrumented to produce drive cycle and hydraulic duty cycle data. This data was used to understand vehicle operation and to validate a reverse facing dynamic model of the stock refuse vehicle. A hybrid model was then produces and used in conjunction with a non-linear optimization algorithm to determine the potential benefit of this technology. This study concluded that a work circuit hybrid providing energy to the arm of a side loader refuse vehicle could achieve a 2.3% reduction in fuel consumption with a 4 year payback period using optimally sized hybrid components. The fuel usage reduction for these hybrids is limited to how well the available energy from regenerative braking is matched with the energy required by the work circuit. For this study, only 16% of the braking energy was utilized due to the selection of vehicle and hydraulic circuit. Work circuit hybrids also enable the use of an idle stop control logic, creating a unique opportunity to combine these two technologies yielding a fuel savings of 21.6% for the same vehicle. There are still some challenges to overcome before this technology can be truly understood. One such challenge is the fact that these hybrids require control of the torque converter lock up clutch and the transmission shifting strategy to make an engine driven configuration feasible. Implementing idle stop may also have hidden challenges including energy losses and emissions issues. However, it is the conclusion of this study that work circuit hybrids do offer a unique set of desired characteristics that warrant further development for future use in the field.
Keywords: hybrid; hydraulic hybrid; idle stop; pressure assist; refuse vehicle; work circuit